Role of flexible fiberoptic nasopharyngolaryngoscopy and indirect laryngoscopy in the diagnosis of laryngopharyngeal pathologies - Feshan, Musarrat; Puthukudy, Preetham A.; Odayappan, Alagammai (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Visualization of the larynx and pharynx is essential to diagnose and treat pathologies, and to prognosticate. This can be done by using indirect laryngoscopy, rigid and flexible endoscopy, and direct laryngoscopy. The main purpose of the article was to assess the profile of laryngopharyngeal pathologies diagnosed by flexible fiberoptic nasopharyngolaryngoscopy and indirect laryngoscopy in patients with laryngopharyngeal symptoms and to estimate the level of agreement between flexible fiberoptic nasopharyngolaryngoscopy and indirect laryngoscopy for selected laryngopharyngeal conditions like vocal nodule, vocal cord polyp, Reinke’s edema, hypopharyngeal growth, vocal cord palsy, vocal cord growth. An Independent t-test and chi-square test were used to analyze the results. Statistical package for the social sciences (SPSS) version 20 was used for statistical analysis. Methods: In this descriptive cross-sectional study, 101 patients with laryngopharyngeal symptoms were subjected to both indirect laryngoscopy and flexible fiberoptic nasopharyngolaryngoscopy. The structures visualized, pathologies detected, time taken and discomfort levels were statistically analyzed. Results: In our study, we found that laryngopharyngeal symptoms were more common among the 61 to 70 years age group. The majority of them were males. The majority of them were retired employees. The most common presenting complaint was difficulty in swallowing, followed by globus sensation and voice change. All structures were visualized by flexible fiberoptic nasopharyngolaryngoscopy. Whereas, in indirect laryngoscopy, some structures were visualized and some were not. Pyriform fossa apex and post-cricoid region were not visualized for all patients with indirect laryngoscopy. Laryngopharyngeal reflux was the most common pathology detected. There is no significant difference between IDL and FOL in site, subsite, and clinical appearance of the pathology detected. There is a significant difference between IDL and FOL in time taken (FOL has a higher mean) and discomfort levels (IDL has a higher mean). Conclusions: Though indirect laryngoscopy is cost-effective in terms of investment, the time taken for the procedure is also less, flexible fiberoptic laryngoscopy is considered superior because it can visualize all structures and can detect pathologies early in their stage so that the patient gets treatment early which can alter the prognosis.